2017
DOI: 10.20950/1678-2305.2017.85.92
|View full text |Cite
|
Sign up to set email alerts
|

Hidrolisado proteico de peixe em dietas para juvenis de Arapaima gigas

Abstract: This study evaluated the dietary inclusion of a fish protein hydrolyzate (FPH) derived from tilapia trimmings on physiological and growth parameters of juveniles of Arapaima gigas. A total of 180 arapaima juveniles (91.4 ± 2.7 g) were used in a complete randomized design with six treatments (n = 3). Fish were fed to apparent satiation four times a day for eight weeks, with diets containing increasing inclusion levels of FPH (0, 4, 8, 12, 16 and 20%). FPH diets did not affect growth and hemato-biochemical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…The RBC is crucial for oxygen transport throughout the body, ensuring proper tissue function. In addition, earlier studies discovered that various levels of protein hydrolysate supplementation in fish diets affect the HGB, HCT, MCV, MCH, and MCHC levels, similar to the current study findings [75,76,[78][79][80]. These are essential parameters in an aquaculture species as indicators of health and physiological status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The RBC is crucial for oxygen transport throughout the body, ensuring proper tissue function. In addition, earlier studies discovered that various levels of protein hydrolysate supplementation in fish diets affect the HGB, HCT, MCV, MCH, and MCHC levels, similar to the current study findings [75,76,[78][79][80]. These are essential parameters in an aquaculture species as indicators of health and physiological status.…”
Section: Discussionsupporting
confidence: 89%
“…Monocytes are responsible for pathogen phagocytosis and assist in immune response, eosinophil modulates inflammation, and basophil contributes to allergic reactions in fish. Earlier studies also reported similar outcomes with various levels of FPH in Arapaima gigas [75], Penaeus monodon [76], and O. pabda [1].…”
Section: Discussionsupporting
confidence: 67%
“…This increase in triglycerides may be linked to high amounts of carbohydrates in the diet related by Silva et al (2020), which was not found in the present study. Ribeiro et al (2017) did not observe changes in the hematological and biochemical parameters of A. gigas fed for 60 days with diets with up to 20% inclusion of the fish protein hydrolysate and suggested this formulation as an adequate supplement to the diet of these fish.…”
Section: Discussionmentioning
confidence: 78%